Analisis Strategi Digital Marketing Dan Inovasi Produk Untuk Meningkatkan Penjualan Produk UMKM Di Kabupaten Bojonegoro - Irnawati, Dwi; Anggapratama, Reza; Saputra, Muhammad Yoga Aditya; Cahya, Kevin Dwi Nur (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
In achieving company goals through product marketing, an appropriate marketing strategy is needed. Products must continue to innovate to match the direction of the marketing media used. Digital marketing has become a common choice for companies and MSMEs. Both on a micro and macro scale, digital marketing is considered an effective strategy to introduce products to the wider community. Creating efficient marketing flows and continuously innovating products, companies can increase profits and sales significantly. This study aims to evaluate the influence of digital marketing and product innovation on increasing product sales. The method used in this study is using a discriptive quantitative approach, the population in the study is producers and consumers of RENA Fashion Bojonegoro which amounts to 18 people from producers and 1,005,671 people from consumers. Then for sampling using the slovin formula to produce a sample of 97 people, and the data analysis technique used is using SPSS 22. RENA Fashion Bojonegoro was the subject of research. The results showed that digital marketing and product innovation either together or individually had a positive effect on increasing product sales